Ecofeminism in Patricia McCormick’s Sold: Parallels between the Exploitation of Women and Nature - Thapa, Hukum (JODEM: Journal of Language and Literature, 2025)
This research paper examines the exploitation of women and nature through the lens of ecofeminism in Patricia McCormick’s Sold. It analyzes the conditions of the girl protagonist Lakshmi’s village home and the roles of males, particularly her stepfather. The studyfurther investigates her forced sale to an Indian brothel, focusing on the roles of its owner and clients. It seeks to answer how patriarchal and capitalist economic structures perceive women and nature, how both are regarded as inherently pure until exploited, and how Lakshmi and nature demonstrate resilience. To address these questions, this paper draws on the ideas of ecofeminist theorists such as Vandana Shiva, Carolyn Merchant, Val Plumwood, Greta Gaard, and Maria Mies. The study concludes that Sold illustrates the parallels between the exploitation of women and nature, showing that patriarchal and capitalist systems treat them as subjects to be colonized, while also highlighting their resistance and resilience. Finally, this research opens avenues for further investigation into girl trafficking and broader patterns of exploitation.